Impact of soil amendments on macronutrients (NA, K, CA, MG, N and P) contents of rice grain under subsurface drainage in salt affected soil - Mandal, R; Aich, AC (Dhaka University Journal of Biological Sciences, 2011)
Impact of soil amendments and brackish water irrigation on grain of three cultivars of rice provided with subsurface drained and non-drained conditions in saline soil was investigated. Contents of Na, Mg, N and P of rice grain increased significantly with increasing brackishness of irrigation water (ECiw 0.7 to 5.0 dS/m) irrespective of drainage condition. The content of Na was found much lower in grain provided with subsurface drainage as compared with non drained ones irrespective of treatments and varieties. However, a reverse trend was observed in case of K. Addition of both lime and gypsum alone caused a decrease in Na and an insignificant increase in Ca concentration at all levels of brackish water irrigation. Effect of lime and gypsum in presence of organic matter did not influence very much in Na, Ca and Mg concentrations in all the cultivars. The contents of N and P increased with increasing levels of salinity might be due to stunted growth of plant caused by excessive Na. Lime and gypsum alone caused a decline in the P content whereas organic matter alone helped to increase the same in grain of rice. Application of lime and gypsum along with organic matter failed to respond in P content significantly in grain of rice in all grades of brackish water whether provided with subsurface drainage or not. In both the sets, cow-dung influenced better performance than straw in mineral nutrition of rice grain. Key words: Soil amendment, Rice grain, Macronutrients, Subsurface drainage, Salt affected soil DOI: http://dx.doi.org/10.3329/dujbs.v19i1.8938 DUJBS 2010; 19(1): 1-11